2019
DOI: 10.1186/s12974-019-1685-z
|View full text |Cite
|
Sign up to set email alerts
|

Time course of neuropathological events in hyperhomocysteinemic amyloid depositing mice reveals early neuroinflammatory changes that precede amyloid changes and cerebrovascular events

Abstract: BackgroundVascular contributions to cognitive impairment and dementia (VCID) are the second leading cause of dementia behind only Alzheimer’s disease (AD); however, VCID is commonly found as a co-morbidity with sporadic AD. We have previously established a mouse model of VCID by inducing hyperhomocysteinemia in both wild-type and amyloid depositing mice. While we have shown the time course of neuropathological events in the wild-type mice with hyperhomocysteinemia, the effect of amyloid deposition on this time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
39
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 40 publications
7
39
3
Order By: Relevance
“…Overall, the cytokine data are consistent with previous studies that indicate an enhancement of proinflammatory responses in either WT or AD model mice in response to HHcy [20][21][22]32]. Despite this, the magnitude of the effect appears to be much smaller in the present case, and there are several possibilities for this apparent discrepancy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, the cytokine data are consistent with previous studies that indicate an enhancement of proinflammatory responses in either WT or AD model mice in response to HHcy [20][21][22]32]. Despite this, the magnitude of the effect appears to be much smaller in the present case, and there are several possibilities for this apparent discrepancy.…”
Section: Discussionsupporting
confidence: 92%
“…This implies that interstitial levels of soluble Aβ are being kept in equilibrium via increased plaque formation, consistent with the notion that sequestration into plaques can be a protective response against the more toxic soluble Aβ species [ 31 ]. Our data align with the hypothesis that HHcy can enhance AD risk by increasing overall amyloid burden, a finding that has been replicated across models of AD and under different methods of HHcy-induction [ 21 , 32 34 ]. Importantly, this appears reflective of what occurs in patient populations, where plasma Aβ positively correlates with homocysteine levels and elevated Hcy is also associated with higher brain Aβ accumulation and CAA pathology [ 35 38 ].…”
Section: Discussionsupporting
confidence: 86%
“…It is worth noting, however, that at least one study has observed an increase in plaque-associated dystrophic neurites in association with reduced CCL3 [33] which suggests that its upregulation can in some cases be protective, although this may be a correlative rather than causative effect. In any event, the cytokine data herein are in contrast to previous studies that have reported a robust pro-inflammatory response to this diet in either WT or AD model mice [12][13][14]22].…”
Section: Different Methods Of Hhcy-induction In Various Mouse Models contrasting
confidence: 99%
“…amyloid burden in parenchyma and vasculature [13,[22][23][24]. This is reflective of what occurs in patient populations, where plasma Aβ positively correlates with homocysteine levels and elevated Hcy is also associated with higher brain Aβ accumulation and CAA pathology [25][26][27][28].…”
Section: Different Methods Of Hhcy-induction In Various Mouse Models mentioning
confidence: 89%
See 1 more Smart Citation